SIVA1 Regulates the Stability of Single-Stranded DNA-Binding Protein 3 Isoforms - Yin, Z; Zhang, K; Peng, X; Jiang, Z; Yuan, W; Wang, Y; Li, Y; Ye, X; Dong, Y; Wan, Y; Ni, B; Zhu, P; et al. (Molekuliarnaia biologiia, 2018)
The assembly of LIM-homeodomain (LIM-HD) transcriptional complex plays important roles in early neuronal development. The stability of LIM-HD is controlled by single-strand binding protein 3 (SSBP3) via a cascade mechanism protecting it from proteasomal degradation. The expression level of SSBP3 has to be precisely regulated. Although a decrease of SSBP3 level is associated with several diseases, the mechanism of SSBP3 downregulation and whether SSBP3 itself is subject to proteasomal degradation remain largely unknown. Two strongly conserved transcripts of the SSBP3 gene, SSBP3a and SSBP3c, were cloned from a human brain cDNA library. By RT-PCR, we show that Ssbp3c is continuously expressed in both embryonic and adult mouse brain, whereas Ssbp3a is restricted to embryonic brain tissue. By co-IP and GST pulldown assays, we identified SIVA1 as a novel SSBP3-binding factor. In a ubiquitination assay, we show that SIVA1 enhances the ubiquitination of SSBP3 and regulates its abundance. Our findings reveal the proteasomal degradation of SSBP3 for the first time and provide a rationale for an SIVAl-SSBP3-dependent mechanism for the disassembly of LIM-HD multiprotein complexes.